Peningkatan Daya Saing Produk Jamur Tiram di Desa Srikandang Melalui Inovasi Strategi Pemasaran Digital dan Desain Kemasan - Choeri, Imron; Ariyanti, Diana Putri; Auliya, Ceaciellya Dhaiya’ul (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2024)
Oyster mushrooms (Pleurotus Ostreatus) are increasingly in demand in Indonesia due to their ease of cultivation and economic benefits. Oyster mushroom cultivation, which can be carried out throughout the year, does not require large areas of land, and utilizes easily obtained raw materials, provides advantages in the context of urban and rural agriculture and environmental sustainability. However, entrepreneurs in Srikandang Village, Jepara Regency, face challenges in conventional marketing and unattractive packaging design. This research used a qualitative case study approach to identify and develop digital marketing strategies and packaging design improvements. Results show that innovations in packaging design and logo, as well as the implementation of digital marketing strategies through social media, can improve product competitiveness and expand market reach. The implementation increased sales by 20 per cent in three months and improved the digital skills of the entrepreneurs. The programme also brought about positive social and cultural changes, with local communities appreciating digital marketing and packaging design more. The long-term impact is expected to improve the economic and social welfare of the people of Srikandang Village by strengthening the position of oyster mushroom products in the national market.